Theory of the Voltage Clamp of the Nerve Membrane, I. Ideal Clamp - Nó, R. Lorente De (1971)
The mathematical theory of the flow of current during a voltage clamp has been developed for a nerve membrane having constant conductance and for a membrane whose conductance increases during activity. It is found that the published families of voltage clamp records are compatible only with a practically constant membrane conductance.